2002
DOI: 10.7863/jum.2002.21.12.1357
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ultrasound Treatment Increases the Bone Fracture-Healing Rate in an Internally Fixed Rat Femoral Osteotomy Model

Abstract: This study confirms the previously shown efficacy of low-intensity ultrasonic stimulation in acceleration of the normal fracture repair process even when performed with a diagnostic sonographic device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…While ultrasound has been shown to improve radiographic fracture healing and increase bone density in rat femora at intensities as low as 11.8mW/cm 2 , that lay in the range of those used in diagnostic setting (Heybeli et al 2002), there is evidence that, in the range of low intensities (below 100 mW/cm 2 ), the response of osteoblasts to the application of ultrasound is directly related, in vitro, to the applied intensity (Harle et al 2001).…”
Section: Lipus Parameters and Treatment Modalitiesmentioning
confidence: 97%
“…While ultrasound has been shown to improve radiographic fracture healing and increase bone density in rat femora at intensities as low as 11.8mW/cm 2 , that lay in the range of those used in diagnostic setting (Heybeli et al 2002), there is evidence that, in the range of low intensities (below 100 mW/cm 2 ), the response of osteoblasts to the application of ultrasound is directly related, in vitro, to the applied intensity (Harle et al 2001).…”
Section: Lipus Parameters and Treatment Modalitiesmentioning
confidence: 97%
“…Ultrasonography possesses the advantage of being a noninvasive and radiation-free method for this. Studies have shown that more than conventional radiographs, ultrasound with power Doppler clearly reveals healing of fractures along with details of the improvement in vascularity in the affected bone (1,2). These studies prove that high-resolution ultrasound is a very useful tool for monitoring bone healing.…”
mentioning
confidence: 90%
“…These applications are further enhanced by its high-end aspects of color power Doppler to assess blood flow, three-dimensional imaging, and detection of tissue harmonics for improved resolution. Apart from its use as a diagnostic tool, ultrasound is also used in orthopedics for monitoring the healing of fractured bones (1)(2)(3). Ultrasonography possesses the advantage of being a noninvasive and radiation-free method for this.…”
mentioning
confidence: 99%
“…All the information stems from experimental data, 16,17 and precise knowledge of exact values is nonexistent, 18 although some animal evidence exists. 19 The thermal effect, however, can also be beneficial, as in physical therapy and as can be judged by several publications, 20 including the article by Heybeli et al 3 in this issue. It is unlikely that radiation stress and acoustic streaming will have detrimental effects in late pregnancy, but certain stages of embryonic and fetal development may be more susceptible to thermal effects (see below).…”
Section: Can Effects Of Ultrasound In Tissue Be a Biological Hazard?mentioning
confidence: 95%